Conversational AI for Santripreneurs: Enhancing Business Communication Skills in an Informal-Religious Educational Context - Maisarah, Maisarah; Al-Dhahli, Faiza; Setyobudi, Bambang; Masrur, Mukhamad (Jurnal Pendidikan Progresif, 2025)
Conversational AI for Santripreneurs: Enhancing Business Communication Skills in an Informal-Religious Educational Context. Objectives: This paper evaluates the effectiveness of a chatbot-assisted training program in enhancing business communication among young entrepreneurs in Islamic boarding schools (pesantren), referred to as "santripreneurs." While santripreneurs possess strong religious and entrepreneurial values, they face challenges with formal communication tasks, such as email, product promotion, and customer replies. Methods: A quasi-experimental design was employed, and 60 entrepreneurs were purposively selected and assigned to either the experimental or control group. The experimental group received chatbot-assisted training, whereas the control group used classical methods, including textbooks and written exercises. Both groups had undergone pre- and post-tests that assessed clarity, professional tone, accuracy in grammar, format, and audience awareness. The usefulness, ease of use, and confidence were determined through a perception survey. The treatment lasted three weeks and consisted of daily 30-minute sessions. Paired-sample t-tests and ANCOVA were used to analyze the data. Findings: The experimental group showed significantly higher post-test scores than the control group (p < 0.001). Their mean improvement was +18.8 points compared to +8.4 in the control group. The strongest gains were observed in professional tone (+22%) and grammar accuracy (+21%), indicating that chatbot feedback was particularly effective in helping learners write formally and avoid errors. Perception data further supported these results: learners gave mean ratings above 4.5 out of 5, with the highest score (M = 4.7) for “the chatbot assisted me in building my communication skills.” These findings demonstrate that chatbots functioned as interactive learning companions, not merely as digital tools. Conclusion: Chatbot-assisted training is an efficient method for developing business communication skills among santripreneurs in informal and religious contexts. In practice, it is a relatively easy and culturally flexible method of supporting young entrepreneurs in areas where formal education is scarce. By integrating AI into pesantren, teachers will be able to cultivate an inclusive training environment that fosters entrepreneurship, preparing their students to engage more confidently in digital business environments. Educators can foster inclusive entrepreneurship education, equipping learners with skills to participate more confidently in digital business contexts. Keywords: chatbot, business communication, santripreneur, digital learning.